Interactive STEM Talk and Workshop Outreach Programme-By Students, for Students: A Malaysian Context - Chua Y.L.; Choong P.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Engineering education; STEM (science, technology, engineering and mathematics); Surveys; Higher education; interactive talk; interactive workshop; Learning experiences; Malaysians; Secondary schools; STEM education; University students; Students